Rancang Bangun Aplikasi Pembelajaran Bahasa dan Kebudayaan Suku Dayak Berbasis Multimedia - Michael Christianto Salim; B. Yudi Dwiandiyanta; Martinus Maslim (Universitas Atma Jaya Yogyakarta, 2017)
Abstract. Indonesia is a heterogeneous country with many different ethnic groups. Borneo Island has a famous native tribes that belong to Dayak. Among others are ma'anyan people, Dayak Ngaju, Dayak Kualan Sekayok, Dayak Ot Danum, etc. Dayaks have different languages and cultures. To make it easier to learn the languages and cultures of Dayak, it requires a lot of information. Information about the language and culture of Dayak is to increase the users’ knowledge to become more familiar with the languages and cultures of the Dayak tribes. The information of languages and cultures of Dayak is put in the form of multimedia-based learning applications. Language learning applications and multimedia-based Dayak culture are created by the existing multimedia elements such as text, images, sound, video, and animation. The test results show that 96.875% of users agree that the application is eligible to be used as a learning medium of Dayak Tribe.Keywords: Dayak Tribe, Language and culture, Multimedia Abstrak. Indonesia merupakan Negara Heterogen, yaitu negara yang memiliki banyak sekali perbedaan, terutama suku. Di Pulau Kalimantan memiliki suku asli yang terkenal, yaitu Suku Dayak. Diantaranya adalah Suku Dayak Maanyan, Suku Dayak Ngaju, Suku Dayak Kualan Sekayok, Suku Dayak Ot Danum, dll. Suku-Suku Dayak tersebut memiliki bahasa dan kebudayaan yang berbeda. Untuk mempermudah dalam mempelajari bahasa dan kebudayaan Suku Dayak, dibutuhkan informasi mengenai bahasa dan kebudayaan Suku Dayak. Informasi tentang bahasa dan kebudayaan Suku Dayak ini dapat menambah pengetahuan pengguna untuk semakin mengenal bahasa dan kebudayaan Suku Dayak tersebut. Informasi bahasa dan kebudayaan Suku Dayak dituangkan dalam bentuk aplikasi pembelajaran berbasis multimedia. Aplikasi pembelajaran bahasa dan kebudayaan Suku Dayak berbasis multimedia dibuat dengan elemen-elemen multimedia yang ada seperti teks, gambar, suara, video, dan animasi. Hasil pengujian menunjukkan bahwa 96,875% pengguna setuju bahwa aplikasi ini layak untuk digunakan sebagai media pembelajaran Suku Dayak.Kata Kunci: Suku Dayak, Bahasa dan Kebudayaan, Multimedia.